Serum Clusterin as a Tumor Marker and Prognostic Factor for Patients with Esophageal Cancer - Guo, Wei; Ma, Xiao; Xue, Christine; Luo, Jianfeng; Zhu, Xiaoli; Xiang, Jiaqing; Lu, Bo; Li, Hecheng (Disease Markers, 2014)
Background. Recent studies have revealed that clusterin is implicated in many physiological and pathological processes, including tumorigenesis. However, the relationship between serum clusterin expression and esophageal squamous cell carcinoma (ESCC) is unclear. Methods. The serum clusterin concentrations of 87 ESCC patients and 136 healthy individuals were examined. An independent-samples Mann-Whitney U test was used to compare serum clusterin concentrations of ESCC patients to those of healthy controls. Univariate analysis was conducted using the log-rank test and multivariate analyses were performed using the Cox proportional hazards model. Results. In healthy controls, the mean clusterin concentration was 288.8±75.1 μg/mL, while in the ESCC patients, the mean clusterin concentration was higher at 412.3±159.4 μg/mL (P<0.0001). The 1-, 2-, and 4-year survival rates for the 87 ESCC patients were 89.70%, 80.00%, and 54.50%. Serum clusterin had an optimal diagnostic cut-off point (serum clusterin concentration = 335.5 μg/mL) for esophageal squamous cell carcinoma with sensitivity of 71.26% and specificity of 77.94%. And higher serum clusterin concentration (>500 μg/mL) indicated better prognosis (P=0.030). Conclusions. Clusterin may play a key role during tumorigenesis and tumor progression of ESCC and it could be applied in clinical work as a tumor marker and prognostic factor.